2003
DOI: 10.7547/87507315-93-4-298
|View full text |Cite
|
Sign up to set email alerts
|

Hyperbaric Oxygen Therapy for Lower-Extremity Soft-Tissue Sports Injuries

Abstract: Lower-extremity injuries have become increasingly common as sports performance demands have risen. Hyperbaric oxygen therapy is one method used to return athletes to competition as quickly as possible, but it has received criticism and lacks support. This review examines the literature on hyperbaric oxygen therapy and soft-tissue sports injuries. In the various studies, the location of the injury seemed to influence the effectiveness of treatment. Injuries at areas of reduced perfusion such as muscle-tendon ju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…The use of HBO treatments by elite athletes to accelerate recovery from tendon and muscle injuries began to gain popularity in the early 1980s (19). The application of HBO treatments for sports injuries has recently been suggested in the scientific literature as a therapy modality, i.e., a primary or an adjunct treatment (4,6,20,21). However, published studies on the effects of HBO in models of muscle injury are relatively scarce (2,3,5,13,23,29,30), and the results of studies that have investigated the recovery of functional capacity have been inconsistent.…”
mentioning
confidence: 99%
“…The use of HBO treatments by elite athletes to accelerate recovery from tendon and muscle injuries began to gain popularity in the early 1980s (19). The application of HBO treatments for sports injuries has recently been suggested in the scientific literature as a therapy modality, i.e., a primary or an adjunct treatment (4,6,20,21). However, published studies on the effects of HBO in models of muscle injury are relatively scarce (2,3,5,13,23,29,30), and the results of studies that have investigated the recovery of functional capacity have been inconsistent.…”
mentioning
confidence: 99%
“…Regarding HBOT potential risks, this therapy has been shown to be extremely safe during the treatment of several pathologies (Heyboer et al, 2017; Kanhai & Losito, 2003; M. S. Leite et al, 2010; D. Zhao et al, 2017), including orthopedic conditions (Huang et al, 2006). Most complications are minor and reversible.…”
Section: Safety Risks and Uncertainties Of Hbotmentioning
confidence: 99%
“…Hyperbaric oxygen therapy Bis the therapeutic administration of 100 % oxygen at environmental pressures greater than one atmosphere^ [27]. It has been suggested that hyperbaric oxygen therapy can be an effective treatment for muscle crush injuries, muscle contusions, and sports-related injuries [28,29]. The evidence for these benefits comes primarily from studies using animal models [30].…”
Section: Hyperbaric Oxygenmentioning
confidence: 99%